PENGARUH REPUTASI DAN KEPERCAYAAN PASIEN TERHADAP KEPUASAN DAN LOYALITAS PASIEN RAWAT JALAN BPJS DI RUMAH SAKIT ANNISA KOTA TANGERANG - Eneng Wiliana; Lena Erdawati; Yanthi Meitry Gunawan (Prosiding Simposium Nasional Multidisiplin (SinaMu), 2019)
Health services in the hospital today can be done independently or through BPJS financing in the form of outpatient service activities, inpatient services and emergency care services that include medical services and medical support. The purpose of this research is to know and analyze the influence of reputation and confidence in the satisfaction and loyalty of BPJS patients at Annisa Hospital in Tangerang City. The research plan used is Explanatory Research which describes the causal relationship between research variables through the hypothesis testing the data collection techniques used are observation methods, interviews and questionnaires. Related to reputation, relational quality, customer satisfaction trust and customer loyalty. Where the sample used is an outpatient as many as 100 respondents with a questionnaire containing 48 question items. The analysis technique used is Path Analysis. The results showed that there was a strong relationship between trust in patient satisfaction compared to reputation, where both independent variables, reputation and trust had a positive and significant influence on Patient satisfaction and loyalty.Keywords: Reputation, trust, satisfaction, loyalty, BPJS patients